Neural activation in cognitive motor processes: comparing motor imagery and observation of gymnastic movements - Munzert, J.; Zentgraf, K.; Stark, R.; Vaitl, D. (Experimental Brain Research, 2008)
The simulation concept suggested by Jeannerod (Neuroimage 14:S103-S109, 2001) defines the S-states of action observation and mental simulation of action as action-related mental states lacking overt execution. Within this framework, similarities and neural overlap between S-states and overt execution are interpreted as providing the common basis for the motor representations implemented within the motor system. The present brain imaging study compared activation overlap and differential activation during mental simulation (motor imagery) with that while observing gymnastic movements. The fMRI conjunction analysis revealed overlapping activation for both S-states in primary motor cortex, premotor cortex, and the supplementary motor area as well as in the intraparietal sulcus, cerebellar hemispheres, and parts of the basal ganglia. A direct contrast between the motor imagery and observation conditions revealed stronger activation for imagery in the posterior insula and the anterior cingulate gyrus. The hippocampus, the superior parietal lobe, and the cerebellar areas were differentially activated in the observation condition. In general, these data corroborate the concept of action-related S-states because of the high overlap in core motor as well as in motor-related areas. We argue that differential activity between S-states relates to task-specific and modal information processing.